Photobiomodulation Process - Yang-Yi Xu; Timon Cheng-Yi Liu; Lei Cheng (International Journal of Photoenergy)
Photobiomodulation (PBM) is a modulation of laser irradiation or monochromatic light (LI) on biosystems. There is little research on PBM dynamics although its phenomena and mechanism have been widely studied. The PBM was discussed from dynamic viewpoint in this paper. It was found that the primary process of cellular PBM might be the key process of cellular PBM so that the transition rate of cellular molecules can be extended to discuss the dose relationship of PBM. There may be a dose zone in which low intensity LI (LIL at different doses) has biological effects similar to each other, so that biological information model of PBM might hold. LIL may self-adaptively modulate a chronic stress until it becomes successful.